The fourth-generation behavior therapies (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Third-generation manuals of behavioral therapies have advanced the evaluation and application of interventions based on behavioral analysis. Accepted and commitment therapy, functional analytic psychotherapy, dialectical behavior therapy and behavioral activation can be mentioned among the renowned therapies. Since the launch, researchers have been working to socially validate those new therapies through outcome research, such as randomized clinical trials applied to a variety of disorders and behavioral problems. The present article intends to show some limitations in the unidisciplinary applications of these manuals based on the analysis of the consequences of the unrestricted expansion to new problem classes. We retraced the historical path of improvement of these therapies to identify some determining variables in the unidisciplinary expansion work. It was concluded that few papers were published on the integration of third-generation therapies. Contrary to a functionally oriented proposal, the manuals were being studied in disorders and problems for which they had not been originally projected. Finally, rules were offered for the accomplishment of an adequate initial functional case conception as alternative guidelines for a fourth-generation. In addition, we present models for integration consistent with an idiographic case approach.
Keywords: accepted and commitment therapy; functional analytic psychotherapy; dialectical behavior therapy; behavioral activation; integration; fourth-generation behavior therapies